An Analysis of Lexical Relations in the Luca’s Movie Script by Mike Jones and Jesse Andrews - Linda Fitri Ibrahim; Evi Mariana (Malewa: Journal of Multidisciplinary Educational Research, 2026)
This research aims to (1) describe the types of lexical relations in the Luca movie script by Mike Jones and Jesse Andrews and; (2) describe the most dominant lexical relations in the Luca Movie script by Mike Jones and Jesse Andrews. The methodology used was qualitative-descriptive; the data source is the Luca movie script by Mike Jones and Jesse Andrews. For the result of research, the researcher describes as follow: (1) there were eight types of lexical relations in the Luca movie script by Mike Jones and Jesse Andrews as follows: homonym (20), polysemy (2), synonym (113), antonym (57), hyponym (11), meronym (2), member-collection (17) and portion-mass (1), and; (2) the most dominant types of lexical relations in Luca movie script by Mike Jones and Jesse Andrews was synonym (113).